Breaking bad news to patients with cancer: A randomized control trial of a brief communication skills training module incorporating the stories and preferences of actual patients. Issue 4 (April 2017) - Gorniewicz, James; Floyd, Michael; Krishnan, Koyamangalath; Bishop, Thomas W.; Tudiver, Fred; Lang, Forrest
Highlights: We interviewed patients with cancer to learn about their communication experiences. We created/tested a breaking bad news (BBN) communication skills training module. The brief training module used video-recorded segments from our patient interviews. Intervention group students and residents significantly improved their BBN skills. Health education programs could use this to improve communication and patient care. Abstract: Objective: This study tested the effectiveness of a brief, learner-centered, breaking bad news (BBN) communication skills training module using objective evaluation measures. Methods: This randomized control study (N = 66) compared intervention and control groups of students (n = 28) and residents' (n = 38) objective structured clinical examination (OSCE) performance of communication skills using Common Ground Assessment and Breaking Bad News measures. Results: Follow-up performance scores of intervention group students improved significantly regarding BBN (colon cancer (CC), p = 0.007, r = −0.47; breast cancer (BC), p = 0.003, r = −0.53), attention to patient responses after BBN (CC, p < 0.001, r = −0.74; BC, p = 0.001, r = −0.65), and addressing feelings (BC, p = 0.006, r = −0.48). At CC follow-up assessment, performance scores of intervention group residents improved significantly regarding BBN (p=0.004, r = −0.43), communication related to emotions (p = 0.034, r = −0.30), determining patient's readiness to proceed after BBN and communication preferences (p = 0.041, r = −0.28), active listening (p = 0.011, r = −0.37), addressing feelings (p < 0.001, r = −0.65), and global interview performance (p = 0.001, r = −0.51). Conclusion: This brief BBN training module is an effective method of improving BBN communication skills among medical students and residents. Practice implications: Implementation of this brief individualized training module within health education programs could lead to improved communication skills and patient care.